2013
DOI: 10.1021/ol401989e
|View full text |Cite
|
Sign up to set email alerts
|

Bioreduction of Aryl Azides during Mutasynthesis of New Ansamitocins

Abstract: Supplementing a culture of a mutant strain of Actinosynnema pretiosum that is unable to biosynthesize aminohydroxy benzoic acid (AHBA), with 3-azido-5-hydroxy-benzoic acid and 3-azido-5-amino-benzoic acid, unexpectedly yielded anilino ansamitocins instead of the expected azido derivatives. This is the first example of the bioreduction of organic azides. The unique nature of these results was demonstrated when 3-azido-5-amino-benzoic acid was fed to the corresponding AHBA blocked mutant of Streptomyces hygrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
(27 reference statements)
1
18
0
Order By: Relevance
“…During our investigation of mutasynthetic options with ansamycin antibiotics, we reported on a unique and unprecedented reductive property of the geldanamycin producer S. hygroscopicus towards aryl azides. Selected examples were transformed into the corresponding anilines 19. We have now found that A. mediterranei is the second microbial source able to reduce the bioorthogonal functional azido group (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During our investigation of mutasynthetic options with ansamycin antibiotics, we reported on a unique and unprecedented reductive property of the geldanamycin producer S. hygroscopicus towards aryl azides. Selected examples were transformed into the corresponding anilines 19. We have now found that A. mediterranei is the second microbial source able to reduce the bioorthogonal functional azido group (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Selected examples were transformed into the corresponding anilines. [19] We have now found that A. mediterranei is the second microbial source able to reduce the bioorthogonal functionala zido group (Scheme 3).…”
Section: Mutasynthetic Experimentsmentioning
confidence: 93%
See 1 more Smart Citation
“…These components are relatively small, and so metabolic precursors modified with azides and alkynes may be tolerated by the natural biosynthetic machinery of cells. However, certain azides are prone to reduction in the cellular milieu ( Mancuso et al., 2013 ), and the reaction between azides and linear alkynes depends on copper (I) catalysis, which requires optimization to avoid damage to biomolecules ( Hong et al., 2009 ). Strain-promoted reactions between azides and strained alkynes remove the copper dependence ( Agard et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The processing of 3,5‐diaminobenzoic acid ( 8 ) is especially remarkable because this mutasynthon can easily form ammonium salts, which would hamper transfer through the membrane of S. hygroscopicus . Indeed, in related cases such as mutasynthetic experiments conducted with the AHBA(−) mutant strain of the ansamitocin producer Actinosynnema pretiosum , feeding of 8 did not yield any mutaproduct …”
Section: Resultsmentioning
confidence: 99%